Avaliação do uso de atmosferas modificadas em porcionados de suínos - Magalhães, Alex Uzêda de (2006)
The quality of the pork meat is strongly influenced by the existent gaseous composition around it. With the objective of determining the effects of mixtures of gases on meat, steaks of 100g of loin (longuissimus dorsi) and rib of swine was conditioned in plastic packages with high barrier to gases, being injected different concentrations of CO2, N2, O2 and CO. The samples were stored at 4°C for 30 days, making possible the analysis of these atmospheres on parameters as color, odour, microbial flora, pH and lipid oxidation. For this essay, the following treatments were used: 15%O2, 5%CO2 and 80%N2 (T1); 20%CO2 and 80%N2 (T2); 70%CO2, 29,5%N2 and 0,5% CO (T3) and Vacuum (T4), with the packages being opened every 4 days so that the analyses were made. It was observed that the treatment T3 was the one that best conserved the steaks colour of swine. Referring to color, the treatment T3 was the one which presented the best results, differing significantly from the other treatments and maintaining the desirable brilliant red color in meat, demonstrating the influence of CO in this factor of quality. The pork rib, due to its bone structure, presented smaller shelf-life than the loin. This way, the modified atmosphere becomes one more option for the commercialization of red meat.